Modeling of mass transfer of pollutants in the soil - Бойко, Татьяна Владиславовна; Запорожец, Юлия Анатолиевна (Technology audit and production reserves, 2015)
In the article it is presented a study of influence of contaminants that enter the soil taking into account their specific physical and chemical properties on soil taking into account its internal properties and processes (the process of sorption, chemical interaction, etc.). The factors that affect the process of mass transfer of pollutants in the soil are determined. Accounting of these factors in the mathematical model of mass transfer of solutes in the soil will give an opportunity to assess the dynamics of migration of contaminants in the soil during the filtering process. It is proposed a two-dimensional profile mathematical model of waste water filtration process into the depths of soil based on its properties. The implementation of this model will allow to calculate the concentration profile of contaminated substances in the liquid and solid phases at different times, that is obtained an objective understanding of the process of changing the concentration of impurities in the waste water in the process of mass transfer in the soil layer.